OPPORTUNITIES FOR USING INNOVATIVE TECHNOLOGIES IN EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The demands of the digital society are not entirely met by contemporary schooling. The requirement for educational system reform, the changeover to a new system, and the active adoption of pedagogical innovations. The process of creating, introducing, testing, and evaluating innovations in the realm of education that assist in successfully achieving objectives is known as pedagogical innovation. It is vital to include cutting-edge information and technology capabilities into the educational system, as well as research the experience of global education, in order to create an innovative education system. This article provides feedback and feedback on the prospects for the application of innovative technologies in education.